1988
DOI: 10.1007/bf02544517
|View full text |Cite
|
Sign up to set email alerts
|

Cottonseed, protein and oil yields and oil properties as affected by nitrogen and phosphorus fertilization and growth regulators

Abstract: Two experiments were carried out at our research center during the 1981 and 1982 seasons on cotton cultivar Giza 75 (Gossypium barbadense L.) to investigate the influence of nitrogen fertilization rates (72, 144 or 216 kg/ha.), phosphorus levels (36 or 72 kg P2O5/ha.) and three growth regulators (IAA, IBA or NAA) applied to cotton plants at 10 ppm and sprayed three times (70, 85 and 100 days after sowing) on protein and oil yields, and oil properties. A randomized complete block design with four replications t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
5
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
5
5
0
Order By: Relevance
“…Seed protein (%) and yield. NAA treatments tended to show a slight seed protein percentage increase ITable 1) which was similar to the results obtained by Sawan et a£ EFFECT OF 1-NAPHTHALENEACETIC ACID ON EGYtYrIAN COOl'ON (3,4). The seed protein yield (kg/ha) was markedly increased because of NAA applications as compared to the control The highest proteinyield was detected at 20 ppm, followed by the 15 ppm level.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Seed protein (%) and yield. NAA treatments tended to show a slight seed protein percentage increase ITable 1) which was similar to the results obtained by Sawan et a£ EFFECT OF 1-NAPHTHALENEACETIC ACID ON EGYtYrIAN COOl'ON (3,4). The seed protein yield (kg/ha) was markedly increased because of NAA applications as compared to the control The highest proteinyield was detected at 20 ppm, followed by the 15 ppm level.…”
Section: Resultssupporting
confidence: 84%
“…The n u m b e r of applications three times, twice, and once was positively effective in the same order. This was in harmony with the results obtained by S a w a n e t cd, (3,4).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…In recent years, a lot of QTL for yield, ber quality and other agronomic traits have been identi ed with SNP marker genetic maps in cotton, including restriction-site associated DNA sequencing (RAD-seq) [11,12], genotyping-by-sequencing (GBS) [13,14], ampli ed fragment sequencing (SLAF-seq) [15][16][17][18], and SNP-array [19]. In addition to ber, cotton is also regarded as the most important source of vegetable protein and oil [20,21]. Previous study has demonstrated that the negative relationship exists between cottonseed oil content and ber yield [22], and cottonseed oil content is also negatively related to seed protein content [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Nelson (1949) [53] and Sawan et al (1988) [54] showed that cotton yield and cottonseed N concentration increased linearly with increasing N fertilizer rates. Saleem et al (2010) [43] showed that the maximum seed cotton yield per plant, and seed cotton yield kg/ha were (69.3 g, 3002.4 kg) respectively recorded when nitrogen was applied at the rate of 120 kg•ha [28] found that application of 225 kg•ha −1 nitrogen fertilizer produced the maximum yield (1731.06 kg), the highest number of bolls per plant (5.61), while the maximum boll weight observed in 150 kg•N•ha −1 (9.18 g).…”
Section: Cotton Yield and Nmentioning
confidence: 99%